Switzerland : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Switzerland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Switzerland is affected by the global crisis through the stock effect, the flow effect, and the trade effect. Along with a sharp contraction in exports, investments are now being postponed. Consumption has held up well so far, but as unemployment rises, household spending will lose momentum. The Swiss National Bank has appropriately loosened monetary policy, bringing the policy rates almost to zero. Maintaining financial stability will be essential for ensuring macroeconomic stability and growth in Switzerland.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet